Topical Analysis of Nuclear Experts' Perceptions of Publics, Nuclear Energy, and Sustainable Futures - Patenaude, Hannah K.; Bloomfield, Emma Frances (Frontiers in Communication, 2022)
Nuclear energy experts consider commercial power from fission to be a strong contender to help mitigate the increasing effects of climate change, in part due to its low-to-no carbon emissions. Nevertheless, nuclear energy’s history, including meltdowns such as Three Mile Island, Chernobyl, and Fukushima, and dumping in sacred Indigenous land such as Yucca Mountain, raises important concerns in public deliberation over nuclear power. These communicative dynamics are crucial to study because they inform larger conversations in communication scholarship about the role of experts in scientific controversies and the complicated nature of public trust in and engagement with science. Thus, this study explores the perspectives of experts and how they make sense of their own communicative practices through a topical analysis of semi-structured interviews with twelve nuclear scientists and engineers in the United States and Canada. Our analysis revealed four major topoi: (1) risk and safety, (2) government and policy, and (3) public education and engagement, and (4) cost, along which nuclear experts make sense of science-public boundaries and their role as scientists and scientist-citizens. This paper extends our understanding and how scientists view themselves as communicative actors and the barriers and opportunities for how we can foster productive technical-public relationships around climate change solutions.